(3GdgGTejI aj eYQaI GdefGRd hGdSGYGJ ddjd hTghQ GdaQS heYQaI GdHQhLs
(3ChdgG (B:s
(3Cbhd hbhd GdUOb ai GdfaS ChbY hai GdMb eG jUZi Edjg hjSeY s
(3BNQgG (B:s
(3hQHc QH hGMO djS ZjQg Edjg CehQ GdNdb JeVi hJQLY s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3bUjOI YjfjIs
(3cJH YfhGf GdbUjOI HGdMeQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
Keywords: (3Gdadcs